Toxic Effects of Prodigiosin Secreted by Hahella sp. KA22 on Harmful Alga Phaeocystis globosa - Zhang, Huajun; Wang, Hui; Zheng, Wei; Yao, Zhiyuan; Peng, Yun; Zhang, Su; Hu, Zhong; Tao, Zhen; Zheng, Tianling (Frontiers in Microbiology, 2017)
Application of algicidal compounds secreted by bacteria is a promising and environmentally-friendly strategy to control harmful algal blooms. Years ago prodigiosin was described as an efficient algicidal compound, but the details on the interactions between prodigiosin and algal cells are still elusive. Prodigiosin shows high algicidal activity on Phaeocystis globosa, and it could be used as material to control harmful algal blooms. When algae were treated with prodigiosin at 5 μg/mL, algae cells showed cytoplasmic hypervacuolization, chloroplast and nucleus rupture, flagella missing, and cell fracture, when observed by scanning electron microscope and transmission electron microscopy. Prodigiosin induced a reactive oxygen species burst in P. globosa at 2 h, which could result in severe oxidative damage to algal cells. Chl a fluorescence decreased significantly after prodigiosin treatment; about 45.3% and 90.0% of algal cells lost Chl a fluorescence at 24 and 48 h. The Fv/Fm value, reflecting the status of the photosystem II (PSII) electron flow also decreased after prodigiosin treatment. Quantitative PCR analysis psbA and rbcS expression indicated that photosynthesis process was remarkably inhibited by prodigiosin. The results indicated that the inhibition of photosynthesis may produce excessive reactive oxygen species causing cell necrosis. This study is the first report about algal lysis mechanism of prodigiosin on harmful algae. Our results could increase our knowledge on the interaction between algicidal compounds and harmful algae, which could lead to further studies in the microcosm.